The Image of Public Officials in the Headline "Hedonic Officials: The Seed of Corruption That Butchers the Prosperity of the People" in Online Mass Media - Kusumawati, Nira; Liliani, Else; Zamzani, Zamzani (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2023)
In recent years, online mass media has made a significant contribution to explaining events and how these events are interpreted and understood by the public. One of them is the incident regarding the case of public officials with a lifestyle of hedonism (those familiar with corrupt behavior). The purpose of this study is to examine the image of officials built by the Tirto.id mass media in an editorial on "hedonic officials.â€ The analysis in this study uses qualitative methods. Data analysis was carried out descriptively. This type of research is content analysis with the data source in the form of news text produced and published by the mass media Tirto.id on March 15, 2023. The discourse is entitled "Hedonic Officials: The Seed of Corruption That Butchers the Prosperity of the People.â€ Data collection techniques were carried out by reading discourses and noting excerpts of sentences related to research problems. The research procedure was carried out using three stages (methods) suggested by Norman Fairclough: description, interpretation, and explanation. The validity of the data was carried out by testing referential validity and intra-rater reliability (observing and reading data carefully and persistently). The results of the analysis show that the Tirto.id mass media gives a negative image to several public officials, especially the Directorate General of Taxes (DGT). This negative image can be seen from the use of words that have a negative connotation and contain controversy. Public officials are described as figures who have a hedonistic attitude that is often close to corrupt behavior, entities that are rotten, dirty, disgusting, dilapidated, damaging, and/or butcher people's prosperity